Method of aberration compensation in sapphire optical disks for the long term data storage - Petrov, V.V.; Semynozhenko, V.P.; Puzikov, V.M.; Kryuchyn, A.A.; Lapchuk, A.S.; Morozov, Ye.M.; Borodin, Y.O.; Shyhovets, O.V.; Shanoylo, S.M. (Functional Materials, 2014)
One of the actual problems today is creation of the long term data storage systems. This paper presents the research results that allow implementing technical solution proposed by the authors of this work a few years ago to create the long term storage optical discs based on single crystal sapphire. It is shown that the problem of data reading through the anisotropic substrate can be solved by using the single crystal optical compensating elements. The experimental results confirm an efficiency of the proposed method of aberration compensation for the long term data storage sapphire media.